PENGARUH PENGOLAHAN TANAH SAWAH BEKAS PADI TERHADAP PERTUMBUHAN DAN HASIL KEDELAI - Z Arifin; I R Dewi; D Setyorini; Darman M Arsyad (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2013)
ABSTRACT The Influence of the Former Paddy Soil Cultivation on the Growth and Yield of Soybean. The study aimed to determine the effect of soil tillage on growth and yield of soybean after rice in rainfed lowland. The experiment was conducted in rainfed soil after harvesting of rice in Mojosari Experimental Farm, East Java during late dry season 2012. The soil type is Regosol with 87 m above sea level. The factorial randomized experimental design with two factors and three replications was used. The first factor consists of four varieties, namely: (1) Anjasmoro, (2) Argomulyo, (3) Burangrang, and (4) Kaba. The second factor consisted of three soil preparation (tillage), namely: (1) No tillage, (2) Soil tillage in row of the plant, (3) Soil tillage properly. Plot size was 5 m x 3 m with plant spacing of 40 cm between rows and 15 cm within row with two plant per hill. The fertilizer of Ponska (300 kg/ha) were applied along the rows at the planting time. The analysis of variances showed that most of the soybean characters were not affected by soil tillage system x cultivar interaction, except number of branches at 30 and 72 days after planting and number of seed per plant. Since all characters observed were not affected by soil tillage system, the zero tillage system for growing soybean after rice could be suggested. Seven of eleven characters observed were affected by cultivars, including yield and seed weight. Since both cultivars, namely Anjasmoro and Kaba gave the higher yield (2.6 t/ha) compared to the others, therefore, those cultivars were suggested to the farmers in the areas. Keywords: Soybeans varieties, tillage, rainfed lowlandABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh pengolahan tanah pada beberapa varietas kedelai terhadap populasi gulma, pertumbuhan dan hasil kedelai. Penelitian dilaksanakan di lahan sawah tadah hujan di Kebun Percobaan Mojosari, Jawa Timur pada MK II 2012. Jenis tanah Regosol dengan ketinggian tempat 87 m diatas permukaan laut. Rancangan percobaan acak kelompok faktorial dengan dua faktor dan tiga ulangan. Faktor I terdiri dari 4 varietas, yaitu : (1) Anjasmoro, (2) Argomulyo, (3) Burangrang, dan (4) Kaba. Faktor II terdiri dari 3 olah tanah, yaitu : (1) Tanpa Olah Tanah (TOT), (2) Olah Tanah Baris (OTB), (3) Olah Tanah Sempurna (OTS). Ukuran plot 5 m x 3 m dengan jarak tanam 40 cm antar baris dan 15 cm dalam baris dengan dua tanaman per lubang. Pupuk Ponska (300 kg/ha) diberikan sepanjang baris tanam. Analisis varian menunjukkan bahwa hampir semua peubah tidak dipengaruhi oleh interaksi varietas x sistim oleh tanah, kecuali jumlah cabang pada umur 30 dan 72 hari, dan jumlah biji per tanaman. Oleh karena semua peubah tidak dipengaruhi oleh sistim olah tanah, maka penanaman kedelai setelah padi sawah dapat dilakukan tanpa olah tanah terlebih dahulu. Tujuh dari 11 peubah yang diamati dipengaruhi oleh varietas, termasuk hasil dan bobot 100 biji. Varietas Anjasmoro dan Kaba memberikan hasil tertinggi (2,6 t/ha), sehingga kedua varietas tersebut dapat dianjurkan untuk wilayah/agroekologi yang serupa dengan lokasi penelitian. Kata kunci: Varietas kedelai, olah tanah, gulma, sawah tadah hujan